Constantes biofisicoquímicas del líquido sinovial de bovinos : tensión superficial a distintas temperaturas (Veterinary Science, 2017)
The surface tension of synovial fluid of bovine has investigated in the temperature range between 20,0ºC and 40,0ºC +- 0,1ºC, , at intervals of 5,0ºC. About hundred experiments were performed. Plotting the experimental results of the surface tension as a function of temperature, a linear relationship is seen to be satisfactorily obeyed. The value of "y" at the mean temperature of this specie (38,5 ºC), obtained from graphical interpolation is: y=58,3 dynes . cm-1. This value is considerably smaller than that for pure water at the same temperature and for sodium chloride in aqueous solutions at similar concentration of that present in synovial liquid. There is, thus decrease in the surface tension of the water amounting to about 20 %. The concentration of week electrolytes in the synovial fluid cannot explain this behavior. Because of this fact, we can suggest that decrease owing to the existence of some other substances - like hyaluronic acid-which can contribute to diminished the surface tension of the solvent. In future experiments we will try to confirm this assumption.